As boas famílias e os outros: as elites de São Paulo e a greve geral de 1917 - Walker, José Roberto (2020)
The main objective of this research is to understand the formation and composition of the social groups that were at the forefront of politics and business in São Paulo, between the end of the Empire and the First Republic. It seeks to study the trajectory of the São Paulo elites, seeking to capture their dynamics and internal divisions, which can be clearly perceived at the time of the general strike of 1917. This strike, the largest ever in the city at any time, is a key to understand the changes taking place in São Paulo and in the country at the beginning of the 20th century. During the strike, contrary to what is commonly assumed, the São Paulo elites chose as their main adversary, not the workers and their movement, but the industrialists, almost all foreigners and newcomers, who settled in São Paulo from 1890 on and since then they had been getting rich fast and could put the domination of traditional São Paulo families at risk. The workers, although also foreigners and newcomers, were not yet a force that could be seen as a threat to the dominant social strata. This perception changes in the years following the 1917 strike, especially after a clearer view of the unfolding and consequences of the Russian Revolution was obtained, which were unknown until then. In order to understand the role of São Paulo's dominant groups in this process, we sought to learn in the city's newspapers how the various social actors expressed themselves. In these publications, it is possible to observe in great detail the debates that precede and accompany the development of the strike, mainly from the point of view of São Paulo's elites, whose voice is clearly heard through the city's mainstream press